An increase in neural tube defect notifications, South Australia, 2009-2010 - Joan Scott; Leonie Sage; Anh-Minh Nguyen; Wendy Scheil; Louise Flood (World Health Organization Regional Office for the Western Pacific, 2013)
Introduction: In South Australia, reporting of live births, stillbirths of at least 20 weeks or 400g birth weight, termination of pregnancies and congenital anomalies is mandated. We describe the investigation of an increase in notifications of neural tube defects (NTDs) in South Australia in 2009 and 2010 using data from several surveillance systems. Methods: NTD trend data from 1966 to 2010 were reviewed. Comparisons of pregnancies affected by an NTD in 2009 and 2010 were made with pregnancies affected by an NTD in the period 2003-2008 and with all pregnancies in 2009 and 2010. Statistical analysis was undertaken using Poisson regression, chi-squared or Fisher's exact tests. Results: The prevalence of NTD-affected pregnancies was 1.95 per 1000 births (39 cases) in 2010 and 1.91 per 1000 births in 2009 (38 cases), the highest annual rates since 1991. Case series comparisons indicated women with NTD-affected pregnancies in 2009 and 2010 were less likely to be Caucasian compared with women who had NTD-affected pregnancies in the period 2003-2008. Women born in the Middle East and African region (n = 7) were significantly more likely to have NTD-affected pregnancies in the years 2009 and 2010 (relative risk: 3.03; 95% confidence interval: 1.39-6.62) compared with women born in the Oceania region. Discussion: The increased notifications of NTDs can only be partially explained by the increase in numbers of women from the Middle East and African region, with no other contributory causes revealed. This analysis highlighted areas where prevention efforts should be strengthened and surveillance data improved.